First South American Agathis (Araucariaceae), eocene of Patagonia - Wilf, Peter (2014)
- Premise of the study: Agathis is an iconic genus of large, ecologically important, and economically valuable conifers that range over lowland to upper montane rainforests from New Zealand to Sumatra. Exploitation of its timber and copal has greatly reduced the genus’s numbers. The early fossil record of Agathis comes entirely from Australia, often presumed to be its area of origin. Agathis has no previous record from South America. - Methods: We describe abundant macrofossils of Agathis vegetative and reproductive organs, from early and middle Eocene rainforest paleofloras of Patagonia, Argentina. The leaves were formerly assigned to the New World cycad genus Zamia. - Key results: Agathis zamunerae sp. nov. is the first South American occurrence and the most complete representation of Agathis in the fossil record. Its morphological features are fully consistent with the living genus. The most similar living species is A. lenticula, endemic to lower montane rainforests of northern Borneo. - Conclusions: Agathis zamunerae sp. nov. demonstrates the presence of modern-aspect Agathis by 52.2 mya and vastly increases the early range and possible areas of origin of the genus. The revision from Zamia breaks another link between the Eocene and living floras of South America. Agathis was a dominant, keystone element of the Patagonian Eocene floras, alongside numerous other plant taxa that still associate with it in Australasia and Southeast Asia. Agathis extinction in South America was an integral part of the transformation of Patagonian biomes over millions of years, but the living species are disappearing from their ranges at a far greater rate.